IMPLIKASI PEMBELAJARAN BERBASIS HUMANISTIK PADA PADA PENDIDIKAN AGAMA ISLAM - Rulitawati Rulitawati; Purmansyah Ariadi; Yuniar Handayani; Sri Yanti (Raudhah - Proud To Be Professional, 2024)
Abstract Learning carried out by an educator has certain characteristics so that teachers in packaging learning require skills and theories in learning so that reasoned learning can be accepted by students. The purpose of this study is to describe "How the Implications of Humanistic-based Learning can be applied to students in Islamic learning. This research method is to use library research that will be analyzed and concluded. Research data were obtained from book and journal records. The results of this study examine Combs' theory in the learning process and its implications in learning Islamic Religious Education. Combs theory is a theory of learning about humanizing humans. Learning will be meaningful for students if it has meaning for themselves. Therefore, teachers must be able to understand the behavior of students by understanding their world. If teachers want to change the behavior of their students, it is the teacher's job to try to change their views and beliefs. The results of the expected application of humanistic-based learning a teacher can appreciate the results of the learning side, meaning that a teacher can give awards to students who excel both in reward and with praise. Keywords: Implementation of Learning, Humanistic, Islamic Religion